A case report of an unusual kidney tumor: Mucinous tubular and spindle cell carcinoma - Lakić, Tanja; Ilić, Aleksandra; Živojinov, Mirjana; Ilić Sabo, Jelena; Jeremić, Dimitrije; Grbić, Dragan (Vojnosanitetski pregled, 2021)
Introduction. Mucinous tubular and spindle cell carcinoma of the kidney (MTSCC) is a rare and recently described subtype of renal cell carcinoma (RCC). As its name indicates, the tumor is composed of three morphological structures: tubules consisted of cuboidal cells, spindle cells, and extracellular mucus. Case report. A 59-year-old female patient was admitted to the Emergency Center of the Clinical Center of Vojvodina due to injuries sustained in a traffic accident. After diagnostic procedures, computer tomography (CT) revealed a large asymptomatic cyst of the upper pole of the left kidney as an incidental finding. Four months later, after recovering from traumatic injuries, a control CT confirmed a well-circumscribed tumor, 90 mm in diameter, confined to a kidney, and a radical nephrectomy was performed. Histopathological evaluation showed that the necrotic tumor mass consisted of tubules made of cuboidal cells and cords made of spindle cells separated by pale mucinous material in some areas, while other tumor parts were of dense cellularity without mucin. No atypia was found. Conclusion. MTSCC is a variant of papillary RCC, thus, it is usually mistaken with papillary RCC with sarcomatoid differentiation. Because of the same immunoprofile as papillary RCC, histomorphology is imposed as the gold standard for making the diagnosis. MTSCC is a tumor with a generally favorable prognosis, and complete surgical excision appears to be adequate treatment, but single cases with metastatic disease have been reported. In this case, there were no signs of the disease one year after surgery.
Keywords: kidney neoplasms; carcinoma, renal cell; adenocarcinoma mucinous; diagnosis; nephrectomy; treatment outcome